Cost-effectiveness of once-weekly semaglutide versus dulaglutide and lixisenatide in patients with type 2 diabetes with inadequate glycemic control in Sweden. (3rd October 2019) - Ericsson, Åsa; Fridhammar, Adam
Abstract: Aims: This analysis evaluated the cost-effectiveness of once-weekly semaglutide vs glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in patients with type 2 diabetes (T2D) uncontrolled on metformin or basal insulin in Sweden. Materials and methods: This cost-effectiveness analysis (CEA) was conducted using the Swedish Institute of Health Economics (IHE) Diabetes Cohort Model. Analyses were conducted from the Swedish societal perspective over a time horizon of 40 years. For patients uncontrolled on metformin, dulaglutide was the comparator, and data from the SUSTAIN 7 clinical trial was used. For patients uncontrolled on basal insulin, lixisenatide was chosen as the comparator and data was obtained from a network meta-analysis (NMA). Results: The results show that, in patients with inadequate control on metformin, semaglutide 1.0 mg dominated (i.e. provided greater clinical benefit, and was less costly) dulaglutide 1.5 mg. In patients with inadequate control on basal insulin, semaglutide 1.0 mg dominated lixisenatide. The reduction in costs is largely driven by the reduction in complications seen with once-weekly semaglutide. Limitations and conclusions: It is likely that this analysis is conservative in estimating the cardiovascular (CV) cost benefits associated with treatment with once-weekly semaglutide. In patients inadequately controlled on basal insulin, the analyses vs lixisenatide were based on results from an NMA, as no head-to-head clinical trial has been conducted for this comparison. These CEA results show that once-weekly semaglutide is a cost-effective GLP-1 RA therapy for the treatment of T2D in patients inadequately controlled on metformin or basal insulin, addressing many current clinician, patient, and payer unmet needs in Sweden.